2020
DOI: 10.1038/s41467-020-17781-6
|View full text |Cite
|
Sign up to set email alerts
|

The natural function of the malaria parasite’s chloroquine resistance transporter

Abstract: The Plasmodium falciparum chloroquine resistance transporter (PfCRT) is a key contributor to multidrug resistance and is also essential for the survival of the malaria parasite, yet its natural function remains unresolved. We identify host-derived peptides of 4-11 residues, varying in both charge and composition, as the substrates of PfCRT in vitro and in situ, and show that PfCRT does not mediate the non-specific transport of other metabolites and/or ions. We find that drug-resistance-conferring mutations red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 78 publications
(132 reference statements)
6
78
0
Order By: Relevance
“…PfA-M17 is a 68 kDa cytoplasmic enzyme that forms a homo-hexamer in its active form, with optimal function at neutral pH, similar to the pH of the parasite cytoplasm (20)(21)(22). Mathew et al (2021) recently confirmed the cytoplasmic localization of PfA-M17, which supports the proposition that hemoglobin-derived peptides are exported from the DV into the parasite cytoplasm, either through the chloroquine-resistance transporter or by other unidentified mechanisms (23). Once in the cytoplasm, it is believed that hemoglobin-derived peptides are digested by PfA-M17, however, it is also possible that PfA-M17 plays an additional role in the catabolic turnover of peptides from other origins.…”
Section: Introductionmentioning
confidence: 68%
“…PfA-M17 is a 68 kDa cytoplasmic enzyme that forms a homo-hexamer in its active form, with optimal function at neutral pH, similar to the pH of the parasite cytoplasm (20)(21)(22). Mathew et al (2021) recently confirmed the cytoplasmic localization of PfA-M17, which supports the proposition that hemoglobin-derived peptides are exported from the DV into the parasite cytoplasm, either through the chloroquine-resistance transporter or by other unidentified mechanisms (23). Once in the cytoplasm, it is believed that hemoglobin-derived peptides are digested by PfA-M17, however, it is also possible that PfA-M17 plays an additional role in the catabolic turnover of peptides from other origins.…”
Section: Introductionmentioning
confidence: 68%
“…CQ is able to move through biological membranes and accumulate in the acidic digestive vacuole (Ehlgen et al, 2012). This digestive vacuole functions to conduct Polymorphism at position 76 (K76T) in the first transmembrane domain (Pulcini et al, 2015) Digestive vacuole (Shafik et al, 2020) Mutant Pfcrt-mediated CQ efflux lessens access of CQ to its heme target (Ecker et al, 2012) pfmdr-1 [located on chromosome 5 (Ikegbunam et al, 2019)]…”
Section: The Mechanisms and Contributing Factors Associated With Antimalarial Drug Resistance In Plasmodium Falciparummentioning
confidence: 99%
“…Broad-specificity multidrug efflux pumps are an apparent exception, and these have binding cavities with multiple sites that can interact with diverse antimicrobials ( Du et al, 2018 ). Other rare examples of bispecific or multispecific unidirectional transport have been reported in bacteria and eukaryotes, such as siderophore export by multidrug efflux pumps, antibiotic entry through an asparagine importer, and chloroquine transport by a plasmodium peptide transporter ( Hannauer et al, 2012 ; Smith et al, 2019 ; Shafik et al, 2020 ). By contrast, bidirectional ABC transporters that import one substrate and export another, are compatible with the mechanistic models but are unknown.…”
Section: Introductionmentioning
confidence: 99%